Auditory characteristics of individuals with temporomandibular dysfunctions and dentofacial deformities - Tatiane Totta; Giselda Santiago; Eduardo Sanches Gonçales; Sandra de Oliveira Saes; Giédre Berretin-Felix (Dental Press Editora, 2013)
OBJECTIVE: To investigate whether there is any relationship between otological as well as vestibular symptoms, audiological findings and type of temporomandibular disorder (articular, muscular and mixed); and to check the distribution of the temporomandibular disorders (TMD) dysfunction degree in the research population. METHODS: A retrospective study involving 30 patients of both sexes, aged between 18 and 49 years old, diagnosed with TMD and dentofacial deformities, who were subject to clinical evaluation (muscle palpation, auscultation of temporomandibular joint during mandibular motion and measurement of jaw movement), audiological testing (pure tone audiometry and immittance testing) and two questionnaires, one on otological and vestibular symptoms and the other on TMD anamnesis. Based on both the anamnesis questionnaire and the clinical assessment, the subjects were divided according to the type and degree of TMD dysfunction (mild, moderate and severe), and compared regarding the occurrence of auditory signs and symptoms, vestibular symptoms and audiological findings according to TMD type. RESULTS: The anamnesis questionnaire demonstrated higher prevalence (83.33%) of severe TMD. Subjects with mixed TMD had more complaints about hypoacusis than those with muscular TMD (p < 0.05). The results showed no change in either audiological and immittance testing for all assessed individuals. CONCLUSION: Otological symptoms are present in subjects with TMD and dentofacial deformities, regardless of the classification of TMD (articular, muscular or mixed). Those with mixed TMD may have higher incidence of complaints about hypoacusis than subjects with muscular TMD. Further studies are needed to investigate the relationship between otological symptoms and the different types of TMD.